PENYULUHAN TENTANG COVID-19 DI DESA PICUNGPUGUR KECAMATAN LEMAHABANG KABUPATEN CIREBON - Muhamad Robi Sugianto; Nurwaningsih Nurwaningsih; Selvia Andreyani; Septiyani Nuramalia; Siti Nuraeni; Siti Rosidah; Taufik Ismail Huda (Swadaya: Indonesian Journal of Community Empowerment, 2021)
Since the emergence of a new type of virus called coronavirus (Covid-19) in December 2019, which first spread in the Chinese city of Wuhan, until now it has spread throughout the world, including Indonesia. The Covid-19 pandemic is very unsettling for the people of Indonesia, all aspects of life are affected by this pandemic, both in terms of economy, health, education and religious activities are not running as they should, so big the impact felt from the Covid-19 pandemic, but oddly there are still many The Indonesian people who are indifferent to the spread of this virus, there are still many of them who do not care about the calls of the government (central and regional) to break the chain of spreading Covid-19. With that, we, the UMC 2020 KKM PIGUR Group, was moved to help the Cirebon district government, especially in Picungpugur Village, Lemahabang District in campaigning for the dangers of spreading Covid-19, we approached the people of Picungpugur Village, Lemahabang District, through seminars on the dangers of Covid-19, and campaigning to them about the adaptation of new habits recommended by local governments. We also taught them through the approach of distributing masks, making sinks, how to wash their hands properly and installing posters related to the Covid-19 problem in strategic places. The optimization efforts that we are doing are solely to become an extension of the regional government in educating the public to participate in helping the government in breaking the chain of the spread of Covid-19 which has spread widely in Indonesia. With such great hope that after the Covid-19 link is cut, Covid-19 will disappear in this country, and all aspects of life can return to normal and run as they should. Keywords: Adaptation; New Habits; Covid-19; Pandemic